Program Penanganan Fakir Miskin Di Desa Mulyasari Kota Banjar Provinsi Jawa Barat - Rusmana, Aep; Susanto, Eri; Jemadila, Muhammad Rai; Putri, Nabila Aulia (Jurnal Ilmu Kesejahteraan Sosial, 2023)
Poverty is a condition where a person cannot fulfill their basic needs to achieve a more dignified life. This research aims to explain the program for handling the poor in Mulyasari Village which is directed at three things, namely: 1) managing social problems, 2) mechanisms for meeting needs, and 3) providing opportunities for advancement for the poor. The method used in this research is a descriptive qualitative method with a phenomenological tradition. Determining the research sample used purposive sampling technique. There were 6 research informants consisting of Mulyasari Village officials, poor families who received social welfare services, and Community Social Workers. The data collection techniques used are: 1) in-depth interviews, 2) observation, and 3) documentation studies. Data analysis techniques in this research were carried out by data reduction, data presentation, and drawing conclusions or verification. The social interaction of the people of Mulyasari Village looks very close to the spirit of mutual cooperation. This is in line with Talcott Parson's opinion regarding his functional structural theory. The research results show that the program for handling the poor in Mulyasari Village has been running well, but is not yet optimal. The handling of the poor in Mulyasari Village can be regulated with the Integrated Social Welfare Data (DTKS) document. Mulyasari Village does not yet have a Social Welfare Center service (PUSKESOS). Therefore, planning for future social service mechanisms will be carried out in accordance with the PUSKESOS and SLRT Banjar City mechanisms. Poor people in Mulyasari Village have been given opportunities to advance, namely 1) educational scholarships for children, 2) training activities, 3) access and business capital facilities, and 4) planning a forest educational tourism program.